2003
DOI: 10.1213/01.ane.0000058843.24914.c7
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Parturient with a History of Local Anesthetic Allergy

Abstract: The management of parturients with a strong history of allergy to local anesthetics poses significant challenges to the obstetric anesthesiologist. We recommend that when such patients have a strong desire to receive labor analgesia with local anesthetics, they undergo provocative challenge testing with preservative-free bupivacaine performed in labor and delivery with preparations for emergent cesarean delivery after 24-wk gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Second, since lidocaine has been used successfully in the past for labour analgesia, 9 it was reasonable to agree to use it as an infusion for labour pain. Finally, even though allergy testing is possible, and sometimes recommended, during pregnancy and labour, 10,11 it is still somewhat controversial, 12,13 especially if another agent is known to be safe for the patient. In the consultation, we also suggested avoiding medications that release histamine such as morphine and meperidine.…”
Section: Case Reportmentioning
confidence: 99%
“…Second, since lidocaine has been used successfully in the past for labour analgesia, 9 it was reasonable to agree to use it as an infusion for labour pain. Finally, even though allergy testing is possible, and sometimes recommended, during pregnancy and labour, 10,11 it is still somewhat controversial, 12,13 especially if another agent is known to be safe for the patient. In the consultation, we also suggested avoiding medications that release histamine such as morphine and meperidine.…”
Section: Case Reportmentioning
confidence: 99%
“…Balestrieri et al 15 recently published a report of how they handled a case of suspected "caine" allergy in an obstetric patient. They performed provocative testing in this patient at 38 weeks gestation.…”
mentioning
confidence: 99%
“…33 Sensitivity testing may not be valid during pregnancy and also introduces the risk of fetal sensitization, 34 so it is not recommended by the American Academy of Allergy, Asthma and Immunology. 35 The potential for altered drug responses during pregnancy is highlighted in a thoughtful review by Pleym et al 36 who observed that non-pregnant women have a 20-30% greater sensitivity to muscle relaxants, a 30-40% greater sensitivity to opioid receptor agonists and a 30-40% lesser sensitivity to propofol.…”
Section: Altered Drug Responses In Pregnancymentioning
confidence: 99%